Development of a methodology for enterprise manufacturing excellence - Kannan Prasanna. (2013)
In today’s age of globalization industrial firms face constant challenges from all directions. The companies must be willing to adopt new and innovative strategies to maintain a competitive edge in the global market. The decision making process of a firm has become complicated because it has an impact on the performance of the company. Operations Management Innovation Methodology is a methodology that helps industrial firms in making these strategic decisions. The OMNI Methodology aims to be an overall guide in helping a firm determine its business competitive strategy, gaps and performance targets; identify the operations improvement areas and measure the productivity; generate operations improvement initiatives to achieve productivity gain; and finally to develop the implementation action plan.